A study on a velogenic viscerotropic newcastle disease virus in vitro and in vivo - Lai, Chooi May (1985)
The velogenic viscerotropic Newcastle disease virus or the Asiatic strain has been considered the most virulent strain of Newcastle disease virus. It is commonly found in Southeast Asia and it has been known to cause 100% mortality in susceptible flocks. In spite of this, very little research has been conducted on it as many countries prohibit the handling of this strain of virus. In view of this, a project has been undertaken at Universiti Pertanian Malaysia to study the biological properties, cytopathogenicity and morphogenesis of a locally isolated velogenic viscerotropic Newcastle disease virus and to determine its effects on the trachea of nonvaccinated and vaccinated chickens. The in vitro study has shown that this virus has a mean death time of 66 hours, and an intracerebral pathogenicity index of 1.90. Polykaryocytosis is the principal form of cytopathic effect it produces in chick embryo fibroblasts and cells infected by it haemadsorp red blood cells. This virus plaques in cell culture. Negatively stained virus particles have diameters ranging from 100 to 600 nanometers. Electron microscopy demonstrated that the virus replicates in the cytoplasm of infected cells and aggregates of nucleocapsids are found in the cytoplasm. The virus matures at the cell membrane and is released by budding. The effects of the virus on the tracheal epithelium was evaluated by virus isolation and scanning and transmission electron microscopy. This virus causes severe ultrastructural alterations in the nonvaccinated chickens and it could be isolated from the tracheas of all the infected chickens from day 4 postinfection. None of these chickens survived past day 10 postinfection. In the vaccinated chickens, differences were observed. Besides a delay in the onset and a decrease in severity of the damages, the vaccinated chickens were apparently normal throughout the experiment with no death recorded and virus could only be isolated from some of the chickens from day 6 to 9 postinfection. Complete regeneration of the damaged epithelium was accomplished by day 13 postinfection. This study presents for the first time detailed information on the in vitro properties of a locally isolated velogenic viscerotropic Newcastle disease virus. Such information is useful in differentiating the virus from the vaccine strains present, thereby assisting in the diagnosis of the disease. It also provides a basis for understanding the behaviour of the virus in the host. Information on its replication at the site of entry as well as on the response of the vaccinated and nonvaccinated chickens to the virus suggest not only the importance of vaccination but also the call for a good vaccination programme in the control of the disease. The study has also thrown light on the possible epidemiology of the virus in relation to the poultry industry in Malaysia.